For Every Thing There is a Season and a Time …: The Construction of a Humanoid. A Tribute to Vincenzo Tagliasco - De Rossi, Danilo Emilio; D’Ursi, Annamaria (Frontiers in Bioengineering and Biotechnology, 2014)
“There’s a time to be born, and a time to die; a time to break down, and a time to build up; a time to weep, and a time to laugh; a time to keep silence, and a time to speak…” (Ecclesiastes 3, 2-7). There was a time when automata were designed like clocks. Androids will have the time of their creators, the state of the art in technology, a wealth of experience to draw from, as well as the capacity to carry out actions as being endowed with meaning. The machine will undergo a long period of nurturing, from which it will learn to shape some sort of identity. Machines will lead us to a new kind of humanism.